Association Between Physical Fitness and Cognitive Function in Multiple Sclerosis: Does Disability Status Matter?. (March 2015) - Sandroff, Brian M.; Pilutti, Lara A.; Benedict, Ralph H. B.; Motl, Robert W.
Background . Cognitive impairment is a highly prevalent, poorly managed, and disabling consequence of multiple sclerosis (MS). Exercise training that improves physical fitness represents a promising approach for managing cognitive impairment in persons with MS. There is limited evidence that physical fitness is associated with multiple domains of cognitive dysfunction across levels of MS disability. Objective . This cross-sectional study examined the associations among aerobic capacity, lower limb muscle strength, and cognitive functions in persons with mild, moderate, and severe MS disability. Methods . The sample included 62 persons with mild (n = 20), moderate (n = 21), and severe (n = 21) MS disability. The participants underwent neuropsychological assessments of cognitive processing speed (CPS; Symbol Digit Modalities Test [SDMT]), verbal memory (California Verbal Learning Test-2 [CVLT-2]), and visual memory (Brief Visuospatial Memory Test–Revised [BVMT-R]). All participants further underwent testing for measuring aerobic capacity (ie, peak oxygen consumption) and muscular strength (ie, peak torque of knee flexors and extensors). Results . Aerobic capacity and muscular strength outcomes were associated with SDMT ( r = .35-.41), but not CVLT-2 or BVMT-R ( r < .19) scores in the overall sample. Aerobic capacity ( r = .42) and knee flexor peak torque ( r = .39) were associated with SDMT scores in persons with mild disability, but not in those with moderate ( r < .06) and severe ( r < .14) disability. Conclusions . These results support examining aerobic and resistance exercise training programs for improving CPS, particularly among persons with mild MS disability.